Diversity, challenges and potentialities of tourism with mammals in the Brazilian Amazon - Vidal, Marcelo Derzi (2022)
Containing in its territory one of the greatest biological wealth on the planet, Brazil is among the countries with the greatest potential for wildlife tourism. This article discusses the diversity, main challenges and potentialities of tourism with mammals in the Brazilian Amazon. Through extensive search and bibliographic review, a current overview of the activity is provided and approaches to be adopted are suggested to manage possible existing negative impacts. The results demonstrate that tourism with mammals is focused on a few species and developed in a small number of states in the Brazilian Amazon. Among the potentialities of the activity are the development of environmental awareness and environmental education of visitors, the recovery and conservation of species, the income generation and the strengthening of scientific tourism. On the other hand, the negative impacts are worrying, such as habituation and behavioral changes in species, the illegal maintenance of animals in captivity, the supply of food that is not part of the natural diet of the species and the potential transmission of diseases between fauna and visitors. The intention of this paper is to contribute in the awareness of environmental managers, researchers, visitors and tourism operators about the need to adequately planning interaction with wildlife that can contribute to the satisfaction of visitors, generate income for local communities and conservation of species and their habitat.